Certain Types of K-Spaces - Salman, Zahra Ismaal (Al-Nahrain Journal of Science, 2018)
In this work, we introduce and study several types of K-spaces and several properties of these types are proved. Among the obtained results are the following:1-Let X be any space and Y be a K-space, then every compact map f: X  Y is a closed map.2-Let X be any space and Y be an sK-space, then every compact map f: X  Y is s-closed map.